2021
DOI: 10.3389/fnut.2021.789117
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights Into Processing Approaches and Potential Health Benefits of Goat Milk and Its Products: A Review

Abstract: Goat milk is considered to be a potential source of various macro- and micro-nutrients. It contains a good proportion of protein, fat, carbohydrates, and other nutritional components which help in promoting nutritional and desirable health benefits. Goat milk is considered to be superior in terms of numerous health benefits, and lower risk of allergy, when compared to the milk of other species. Several processing techniques such as pasteurization, ultrafiltration, microfiltration, and ultrasound have been empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 127 publications
1
25
0
1
Order By: Relevance
“…Rumenic acid has been related to positive effects on serum lipid profile, blood glucose, insulin sensitivity, blood pressure, and cardiovascular disease risk factor in humans ( 34 ). Goat milk is mainly used for cheese manufacturing, and milk fat and protein are essential components needed for further processing ( 35 ). Therefore, our results show that using sunflower oil or rapeseed oil could be used in goat diets as a feeding strategy for modulating milk fat quality without negative effects on overall productive traits.…”
Section: Discussionmentioning
confidence: 99%
“…Rumenic acid has been related to positive effects on serum lipid profile, blood glucose, insulin sensitivity, blood pressure, and cardiovascular disease risk factor in humans ( 34 ). Goat milk is mainly used for cheese manufacturing, and milk fat and protein are essential components needed for further processing ( 35 ). Therefore, our results show that using sunflower oil or rapeseed oil could be used in goat diets as a feeding strategy for modulating milk fat quality without negative effects on overall productive traits.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in healthy humans showed that consumption of fermented goats' milk for 3 weeks improved anti-atherogenicity in healthy subjects, prolonging resistance of the lipoprotein fraction to oxidation, lowering levels of peroxidized lipoproteins, oxidized LDL, 8-isoprostanes and glutathione redox ratio, enhancing total antioxidative activity, and altering both the prevalence and proportion of https://doi.org/10.1017/S0007114522002537 Published online by Cambridge University Press Accepted manuscript lactic acid bacteria species in the gut microflora of the (32). A recent review of the literature discussed several health benefits of goat milk and milk-based products including reduction of acute inflammation, lowering exaggerated basal secretion of interleukin (IL)-6, IL-8 and acute response, and modest down-regulation of IL-1 beta and production of tumor necrosis factor-alpha in immune compromised elderly patients (33). Moreover, it was discussed that goat milk and milk-based products improved cholesterol mobilization and controlled its storage in the blood, and had ACE inhibitory activity, particularly beta-lactoglobulin, possessing potential antihypertensive properties (33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the literature discussed several health benefits of goat milk and milk-based products including reduction of acute inflammation, lowering exaggerated basal secretion of interleukin (IL)-6, IL-8 and acute response, and modest down-regulation of IL-1 beta and production of tumor necrosis factor-alpha in immune compromised elderly patients (33). Moreover, it was discussed that goat milk and milk-based products improved cholesterol mobilization and controlled its storage in the blood, and had ACE inhibitory activity, particularly beta-lactoglobulin, possessing potential antihypertensive properties (33).…”
Section: Discussionmentioning
confidence: 99%
“…Goat cheese is an underestimated food with high nutritional value and a promising potential as a functional food for human nutrition [ 29 , 30 , 31 ] with Caciotta and Caprino Nicastrese goat cheeses as characteristic examples [ 1 , 32 ]. Within the EU, France followed by Spain and Greece were listed among the 10 top goat cheese producers representing on average 17.3%, 7% and 7.6% of global production for the period 2015–2017, respectively, despite their collective average goat milk production being only 7.9% for the same period [ 33 ].…”
Section: Introductionmentioning
confidence: 99%